Analyzing Hypertension and Reviewing Epidemiology and How to Overcome it - Susanti, Nofi; Gunadi Aulia, Rizky; Panjaitan, Muhammad Faiz; Andrika, Nuansah (Universitas Ibn Khaldun Bogor, 2024)
Infectious diseases and malnutrition will soon replace non-communicable diseases (NCDs) such as heart disease, cancer and depression as causes of death and disability in developing countries. Cardiovascular disease (31.9%), including hypertension (6.8%) and stroke (15.4%), is the highest cause of death, according to the results of the 2007 Basic Health Research in Indonesia. Hypertension is a condition in which blood pressure in the body’s arteries continuously increases, which can cause serious risks to health such as heart disease, stroke and other organ damage. This article will contain information about hypertension and its management. The method used is literature study by taking existing data and then collecting it in this article. It is hoped that this article will be useful and beneficial for various needs.